Discurso de Benedicto XVI al cuerpo diplomático acreditado ante la Santa Sede, 7 de enero de 2008 - Alonso Marcos, Antonio (UNISCI Discussion Papers, 2008)
The author comments the Address that to the beginning of every year the Holy Father directs the members of the Diplomatic Corps accredited to the Holy See. The Pope divides his intervention in two parts: the first is dedicated to offering an overview of the most worrying international situations related to the peace and the security; and the second one is dedicated to calling on to looking in the natural Law for the base of the human living together, at national or international level, since it is most adapted to the human being.